2006
DOI: 10.1191/0961203306lu2311oa
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of steroid-induced osteonecrosis of femoral head in systemic lupus erythematosus by anti-coagulant

Abstract: Although osteonecrosis of femoral head (ONF) is one of the serious complications in systemic lupus erythematosus (SLE) associated with corticosteroid therapy, there has been few trials of prevention of ONF described. We aimed to prevent ONF in steroid-treated SLE patients using anticoagulant, warfarin, conducting a multicenter prospective study. Sixty newly diagnosed SLE patients requiring 40 mg/day or more prednisolone were alternately assigned to either of two groups; a warfarin group and a control one. Warf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 14 publications
1
40
1
2
Order By: Relevance
“…Several researchers have shown steroid-induced ON can be prevented by medications [6,17,18], and a study that used the same rabbit model as ours reported a reduction in ON frequency to 30% to 40% [16]. Our study showed similar suppressive effects, and no rabbits developed tissue damage due to electromagnetism.…”
Section: Groupsupporting
confidence: 69%
“…Several researchers have shown steroid-induced ON can be prevented by medications [6,17,18], and a study that used the same rabbit model as ours reported a reduction in ON frequency to 30% to 40% [16]. Our study showed similar suppressive effects, and no rabbits developed tissue damage due to electromagnetism.…”
Section: Groupsupporting
confidence: 69%
“…These reactions might be important factor in onset of osteonecrosis of femoral head. Several studies reported that a combination of anticoagulant and lipid-lowering agent showed a significant decrease in the onset of osteonecrosis compared with an anticoagulant or a lipidlowing agent alone in human and animal models (14,15,20). Another report suggested that a high serum PAI-1 level may be a risk factor for the development of osteonecrosis of the femoral head by studying thrombophilis and hypofibrolysis patients (4, 6).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, anticoagulation therapy has been tried for prevention of ION in SLE patients, and warfarin has been modestly beneicial in this respect. One study of 60 SLE patients receiving prednisolone at more than 40 mg/day found that treatment with warfarin signiicantly reduced the onset of ION [31]. Among various physical modalities, extracorporeal shockwave therapy, hyperbaric oxygen, and pulsed electromagnetic therapy have yielded encouraging results, but further large prospective studies will be necessary to conirm these efects.…”
Section: Treatment Of Ionmentioning
confidence: 99%
“…The widespread use of MRI now makes it possible to detect osteonecrotic change in SLE patients soon after administration of glucocorticoid, thus facilitating early diagnosis. Nagasawa et al reported that 33% of patients developed ION within 3 months after the start of glucocorticoid treatment and that symptomatic ION became apparent at 2 years and beyond [31]. Radiographically, a subchondral radiolucency known as the crescent sign appeared at a late stage in ION, indicating subchondral fracture.…”
Section: Timing Of Osteonecrosis-related Ischemia In Patients With Slementioning
confidence: 99%
See 1 more Smart Citation